Mechanical, electrical and thermal properties of in-situ exfoliated graphene/epoxy nanocomposites. (April 2017) - Li, Yan; Zhang, Han; Porwal, Harshit; Huang, Zhaohui; Bilotti, Emiliano; Peijs, Ton
Abstract: Depending on processing conditions, in-situ exfoliated graphite nanoplatelets (GNP) with low defect content and average aspect ratios up to 300–1000 and thicknesses of 5–17 nm could be produced by three roll milling (TRM). This paper focuses on the mechanical, electrical and thermal properties of in-situ GNP/epoxy nanocomposites, evaluated in terms of simple analytical models. Good mechanical reinforcement (160% increase in flexural modulus @ 4 wt.% GNP), electrical conductivity (∼10 −2  S/m @ 3 wt.% GNP with a percolation threshold of 0.52 vol.%) and thermal conductivity (0.70 W m −1  K −1 @ 5 wt.% GNP) were obtained. The production of GNP-filled resins using TRM technology can potentially remove important cost barriers for GNP modified plastics, composites and coatings as compared to traditional multi-step solvent based exfoliation methods.